2014
DOI: 10.1158/1055-9965.epi-14-0605
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Use of NSAIDs and/or Statins Does Not Affect PSA or PSA Velocity in Men at High Risk for Prostate Cancer

Abstract: Background Prostate specific antigen (PSA) and PSA velocity (PSAV, rate of PSA change over time) are biomarkers for diagnosis and prognosis of prostate cancer (PCa). Men who are at high risk for PCa also have associated co-morbidities for which they are taking NSAIDs and statins for long periods; therefore it is important to understand the effect of these medications on markers used to assess PCa risk. Methods Using a population of 699 men, multiple linear regressions were used to investigate the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…High plasma cholesterol levels are linked to the increased risk of prostate cancer in multiple epidemiologic studies [ 50 , 51 , 84 , 85 ]. However, statins that inhibit cellular cholesterol biosynthesis, thereby lower plasma cholesterol, were unable to improve prognosis in prostate cancer patients, suggesting that cholesterol itself might not be the critical factor in prostate cancer development [ 86 , 87 ]. As a major cholesterol metabolite, 27HC has attracted the attention of prostate cancer investigators over the past decade, and it was demonstrated to stimulate the proliferation of RWPE-1 normal prostate epithelial cells in an ER- and androgen receptor (AR)-dependent manner [ 88 ].…”
Section: 27hc and Prostate Cancermentioning
confidence: 99%
“…High plasma cholesterol levels are linked to the increased risk of prostate cancer in multiple epidemiologic studies [ 50 , 51 , 84 , 85 ]. However, statins that inhibit cellular cholesterol biosynthesis, thereby lower plasma cholesterol, were unable to improve prognosis in prostate cancer patients, suggesting that cholesterol itself might not be the critical factor in prostate cancer development [ 86 , 87 ]. As a major cholesterol metabolite, 27HC has attracted the attention of prostate cancer investigators over the past decade, and it was demonstrated to stimulate the proliferation of RWPE-1 normal prostate epithelial cells in an ER- and androgen receptor (AR)-dependent manner [ 88 ].…”
Section: 27hc and Prostate Cancermentioning
confidence: 99%
“…4 However, the serial changes in PSA level did not differ between men receiving atorvastatin and those receiving placebo in this study, a finding consistent with the results of another longitudinal study. 25 Given the long clinical course of prostate cancer, it is difficult to directly compare the effect of statin use on PSA levels following local treatment for other clinical stages, especially in the PSA screening setting. Further studies are needed to determine if statin use affects PSA levels in other stages of the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, sustained use of nonsteroidal anti-inflammatory drugs (NSAIDs) have been proposed as a mechanism that may retard PCa disease progression by decreasing the inflammatory response in PCa cells (25). Observational studies have revealed that NSAIDs are associated with a lower risk of developing PCa (25) and a lower risk of progression to high-grade PCa (26,27), resulting in different NSAIDs being postulated for the treatment of PCa. Clinical trials have been performed with certain NSAIDs (celecoxib, ibuprofen and indomethacin) (5,28), with unsatisfactory results, upon analyzing endpoints such as PSA levels, tumor size or overall survival time (29,30).…”
Section: Decreased Biochemical Progression In Patients With Castratiomentioning
confidence: 99%